The Impact of Using Digital Comic as A Media for Learning Short Stories - Mawarsih, Putri Beny; Hidayati, Ika Emirulliah; Pairin, Udjang; Indarti, Titik (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The aim of this research is to describe the impact of using digital comic as a learning media of Indonesian language subjects for junior high school students. The research method used qualitative method with a case study approach. Data collection uses questionnaires at the beginning of the research process, observations, and interviews with the aim of obtaining information on students’ experiences regarding digital-based learning media. The primary data used is an overview of the use of webtoon applications in learning activities and secondary data in the form of literature studies originating from books, articles, proceedings, theses, and other media that are able to support the availability of information related to related topics. The data that has been collected is analyzed according to the discussion of related topics using data reduction, data display, and conclusion methods. The results of the research show that the majority of grade 7th of junior high school students prefer digital comics compared to using text in conveying short story material. Webtoon-based digital comics are considered more effective and interesting compared to text only. The majority of students understand the story presented using the webtoon application and can answer questions related to the story correctly.